fourth,sixth and thirteenth term in this sequence A(n)= 6+(n+1)(-2) help me to find and describe the explicite formula
1 answer:
Hello,
A(n)=6+(n+1)^(-2)=6+1/(n+1)²
You might be interested in
Answer:
ok....
Step-by-step explanation:
Answer:
2250. hope this helps!
Step-by-step explanation:
Multiply 10 225
Answer:
C. This was hard to do when I had this question
Answer: 13
Step-by-step explanation:
2x-27=-1
2x=26
X=13
Answer:
C
Step-by-step explanation:
The center of the base is the center of the circle
The center of the circle is C